Coordinating attention in a classroom environment which includes both physical and virtual spaces. Issue 1 (2nd January 2020) - Tapio, Elina
ABSTRACT: Through detailed multimodal analyses, this article shows how participants of an English language course create and manage sites of attention for achieving collaboration across multiple spaces. The ethnographic data for the study comes from an English language course 'Academic reading' offered for university students majoring in Finnish Sign Language. The paper examines a classroom situation where the participants interact simultaneously with each other in a chatroom environment and physical environment via several mediational means, such as Finnish Sign Language and typed text in a chatroom that appears on students' tablets and on a large screen in the classroom. The emerging interactional patterns coordinate fragmented interaction into mutual sites of attention so that the participants are able to collaborate. Further, the paper reflects how gaze plays a crucial role in coordinating actions together. Gaze itself is seen as a mediated action which begins to display regularities, and 'comes into being' through long and short life trajectories. The longer trajectory of the mode of gaze is traced to the patterned ways of using gaze in signing communities of practice.